Entre conversas e visualidades: as práticas em artes visuais na educação infantil em instituições públicas da cidade de Guanambi-BA - Freitas, Ana Cláudia de Oliveira (2023)
This study was developed within the Educational Processes in Visual Arts research line, of the Associated Post-Graduate Program in Visual Arts of the Federal University of Paraíba and the Federal University of Pernambuco – PPGAV UFPB/UFPE, based on interests awakened and experienced in the field of art, especially in dealing with Visual Arts with children, whose school attendance becomes mandatory at the age of four accordind to the Brazilian Law No. 12.796/2013 and which I witness daily as a teacher at a public university located in the city of Guanambi, state of Bahia. The present investigation had as problematization: how are the practices in Visual Arts happening in public preschools in the city of Guanambi, State of Bahia? Faced with this issue, we seek to understand how teachers think and practice Visual Arts in preschools at public institutions in the city of Guanambi. For that, we located the Visual Arts in municipal documents that govern Early Childhood Education; we perceived and identified the images and visualities present in the children's school environment, as well as understood the conceptions and practices of Early Childhood Education teachers, specifically in preschool, about Visual Arts, by understanding it as an aesthetic language and as such, a field of knowledge with specific codes that need training and nourishment. With regard to theoretical orientation, we dialogued with authors who discuss the fields of Art/Education, Visual Arts, Visual Culture and Childhood (BARBOSA, 2001; 2004; 2008; 2009; 2010; OSTETTO, 2011; 2018; MARTINS, 1998; 2011; CUNHA, 2005; 2021; DUNCUM, 2010; 2010; CHALMEL, 2004; DEL PRIORE, 2002). As methodological referrals, we used Document Analysis (LÜDKE; ANDRÉ, 2018), Participant Observation (MINAYO, 2010), Conversations as Research Methodology (SOUZA et al., 2019; SERPA, 2010) and insights from Artistic Research Methodology based on in Photography (EGAS, 2018), in two Early Childhood Education establishments settled in the municipality of Guanambi and six teachers, public servants in the municipality, who work in preschool. As recording instruments, we used field diaries, audio recordings and photographs. For our analyses, we chose the Interpretation of Meanings Method (GOMES, 2009). At the end of this study, we conclude that both the official document analyzed, the Guanambi Municipal Curriculum Base, and the participating teachers, recognize the value of the visual arts as an important children's language, however, there are still gaps in the ways of its empirical realization. As for the visualities present in schools, we realize that it is necessary to awaken a sensitive look that leverages existing resources.